(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Gender, marital status, education, income and periodicityof premium exerted significant impact on the level of satisfaction of policy holders in insurance sector. Female and married policy holders were found be more satisfied than male and unmarried policy holders on the performanceof a company. Enhancement in education and income raise the expectations of policy holders, hence lowering down their level ofsatisfaction. Longer periodicity results in enhanced level of satisfaction.Therefore, it is advisable that the insurance companies should evolve suitablepolicies to raise the satisfaction level of their customers.